Data-driven business transformation : how to disrupt, innovate, and stay ahead of the competition - Carruthers, Caroline; Jackson, Peter, 1962- (John Wiley & Sons Ltd, 2019)
Drive your business data to its maximum potential with proven strategies and practical advice The organizations that harness the power of data to transform their businesses will be the market leaders. You can be sure that your competitors will be looking for insights in their data to drive them ahead and that the disruptors in your sector will be data driven. Data, if used correctly, has the power to transform your business and make you the market leader. Data Driven Business Transformation is the practical guide to harnessing your data to compete and thrive in today's dynamic marketplace. This essential resource provides the insight, knowledge and focus you require to transform your business - unlocking the power of data and revealing its hidden value. Delivering step-by-step instructions to every stage of data transformation, this book enables you to strengthen your data literacy and make effective data-driven decisions. Real-world examples of successful data transformations and lessons from people operating in the current data environment provide you with the vision and insight to transform your business. The digital revolution has proven challenging for many businesses. Once viewed as the solution, technology is oftentimes the problem - driving business online but failing to exploit the data to drive operations and value. Authors Peter Jackson and Caroline Carruthers draw from their practical experience as Chief Data Officers to present strategies and methods to unleash the transformational power of data. Emphasising data over digitalisation using data practise and data science, this unique book will assist you to: -Follow concise and pragmatic steps to transition your business to a data-driven model -Apply transformative data principles to any stage of business development -Change the culture of your organisation and place data at the heart of your business -Learn from practicing Chief Data Officers recognized as leaders in the area of data transformation Data Driven Business Transformation: How businesses can disrupt, innovate and stay ahead of the competition is a vital source of guidance for CEOs, Boards, CTOs, CDOs, data change practitioners, programme managers and others in pursuit of data-driven achievement.